Recent Advances in the Nanomaterials, Design, Fabrication Approaches of Thermoelectric Nanogenerators for Various Applications. Issue 35 (25th October 2022) - Kim, Andrew; Kumar, Pawan; Annamalai, Pratheep Kumar; Patel, Rajkumar
Abstract: Thermoelectric nanogenerators (TENGs) are promising sustainable energy devices that utilize thermoelectric (TE) effect of nanomaterials to convert a temperature gradient into electrical energy. Compared to bulk thermoelectric generators (TEGs) that are commercially available, TENGs are more flexible and power‐dense, owing to their tuneable nanostructures. Hence, smaller TENGs are better suited for small form‐factor applications like wearable electronics, internet of things (IoT) devices, and self‐powered sensors. However, the higher complexity and cost of TENGs than TEGs inhibit their widespread adoption. This review appraises the latest advances in TENG materials, design, and fabrication in optimizing the performance of TENGs, making TENGs more viable for real‐world applications. More precisely, this work examines how nanostructure engineering, nanomaterial compositing, and post‐synthesis treatment approaches have enhanced the TE properties of common and promising TE materials, including tellurides, selenides, metal oxides, metal alloys, silicon, carbon nanomaterials, and organic compounds. Given that the TE material is a key component in TENGs, this review highlights how to optimize other vital parameters, including the TENG configuration, contact interface, form factor, heat sink use, and folded shape for specific applications. Lastly, critical attributes of TENGs used in wearable electronics, sensors, implantable electronics, solar energy conversion, and waste heat recovery are analyzed. Abstract : This review analyzes the latest advances in thermoelectric nanogenerator (TENG) materials, design and fabrication for common and promising applications, including wearable electronics, sensors, implantable electronics, solar energy conversion and waste heat recovery. Unlike other earlier reviews, this manuscript focuses on how cutting‐edge nanotechnology has been used to maximize thermoelectric power output and enable the design of flexible and lightweight devices.